(1000) The Use of Commodity Balances in Foreign Trade Planning استخدام أرصدة السلع الأساسية في تخطيط التجارة الخارجية - Dieter Schumeister.; Faika El- Refaie; El-Sayed Dohia; Mohammed Afr. (INP., 2020)
This paper presents the findings of a seminar organized by the International Economic Relations Center at the I.N.P., Cairo, during the visit of Dr. Schulmeister from the German Democratic Republic (GDR). It explores the use of commodity balances in foreign trade planning, drawing on experiences from both the GDR and the Arab Republic of Egypt (A.R.E.)..The discussions among the participants enriched the paper, with valuable insights provided by Dr. Alfonse Azis from the Ministry of Planning and Mr. A. Nousseir from the Department of Commodity Balances. The paper concludes with recommendations for improving foreign trade planning through the effective use of commodity balance methodologies.